Notifiche
Cancella tutti

Integrale

  

0
582

Spiegare e argomentare la risposta.

Autore
1 Risposta



1

f''(x)=- 12·x

f'(x)=

∫ - 12·x dx= - 6·x^2 + a

f(x)=

∫(- 6·x^2 + a) dx = a·x - 2·x^3 + b

f'(-1)=-3:

- 6·(-1)^2 + a = -3---> a - 6 = -3---> a = 3

f(x)=3·x - 2·x^3 + b

∫(3·x - 2·x^3 + b) dx = 

=- x^4/2 + 3·x^2/2 + b·x + c

valutato in x = 2:

- 2^4/2 + 3·2^2/2 + b·2 + c= 2·b + c - 2

valutato in x = -1:

- (-1)^4/2 + 3·(-1)^2/2 + b·(-1) + c=

=-b + c + 1

Deve essere: 

2·b + c - 2 - (-b + c + 1) = 3·b - 3

3·b - 3 = -18---> b = -5

quindi la funzione f(x):

f(x)= - 2·x^3 + 3·x - 5



Risposta
SOS Matematica

4.6
SCARICA